Bizzy Bear Diy day (Somerville, Massachusetts Nosy Crow, an imprint of Candlewick Press, 2018)
Bizzy Bear lends a hand at the fire station and helps put a fire out
Cover title
Rhymes and Songs
Keywords: Bears -- Juvenile fiction; Stories in rhyme; Toy and movable books -- Specimens; Ambulances -- Fiction; Bears -- Fiction; Board books; Stories in rhyme; Toy and movable books